The Effectiveness of Self-Esteem-Related Interventions in Reducing Suicidal Behaviors: A Systematic Review and Meta-Analysis - Dat, Nguyen Tan; Mitsui, Nobuyuki; Asakura, Satoshi; Takanobu, Keisuke; Fujii, Yutaka; Toyoshima, Kuniyoshi; Kako, Yuki; Kusumi, Ichiro (Frontiers in Psychiatry, 2022)
Suicide is a serious social issue and is often treated using psychological interventions. The current systematic review and meta-analysis aimed to investigate the effectiveness of self-esteem-related interventions on suicidal behaviors. A systematic literature search for randomized controlled trials (RCTs) including a self-esteem component was conducted on 29 May 2021 and updated on 4 April 2022. In total, 12 studies were included in the systematic review and five studies were included in the meta-analysis. Small effect sizes were found for suicidal ideation at post intervention (g = -0.24, 95% CI [-0.48, 0.00]) and a 3-month follow-up (g = -0.36, 95% CI [-0.62, -0.11]). However, these results should be interpreted cautiously due to the limited number of included studies and varied sample population. In conclusion, the current review suggests that future intervention studies should incorporate self-esteem enhancement in the treatment of suicidal behaviors, especially for suicidal ideation.